Out-of-Court Assistance Based on the Principle of the Best Interests of the Child: Study on Examination Process of Marriage Dispensation Cases - Ashabul Fadhli; Asasriwarni Asasriwarni; Elfia Elfia; Muhammad Hizbi Islami (JURIS (Jurnal Ilmiah Syariah), 2024)
This research aimed to elaborate the legal phenomenon of marriage postponement proposed by the applicant in the examination process of marriage dispensation cases at the Religious Courts of Bukittinggi. The decision is taken after the applicant receives out-of-court assistance in marriage dispensation cases by other institutions that has been explicitly regulated in the Supreme Court (PERMA) Number 5 of 2019. The purpose of the assistance is to ensure the children’s readiness in entering marriage and the follow up to limited amendment of Article 7 Marriage Law on age limit. This phenomenon is intriguing due to a sizeable finding on previous marriage dispensation cases where most applicants insisted on getting married soon. This field study is descriptive qualitative research applying the descriptive-analysis method. The empirical-juridical approach was employed, analyzing primary and secondary data sourced from interviews and documentations. The collected data were subjected to Creswell’s technique starting from data processing to data interpretation. The results showed that the assistance practice has successfully encourage many child applicants to make decisions based on their best interests, namely postponing the marriage that is facilitated through an integrated system that includes psychological examination, legal approach, and religious approach. Indeed, this system is non-existent in the previous examination process of marriage dispensation cases. Interpretation and realization of Article 15 of PERMA are perceived to have contributed to the decreasing number of marriage dispensation cases in the Religious Courts of Bukittinggi, and establishing PERMA Number 5 of 2019 as the law that guarantees the prevention of child marriage.